Interaction of Customer Satisfaction and Digital Service Retention: Evidence of PLS from Indonesian Islamic Banking - Alfarizi, Muhammad (Universitas Muhammadiyah Yogyakarta, 2023)
The Indonesian Islamic banking sector has been transformed by integrating technology in banking services to satisfy customers for retention and market share post-COVID-19. This study, therefore, investigates the impact of Islamic banking digital service quality post-COVID-19 in Indonesia on customer satisfaction and retention. This study applied the construction of an electronic service quality model (E-S-Qual) and a banking service quality model (BSQ) focusing on digital services in Islamic commercial banks in Indonesia after the COVID-19 pandemic. This study also used an explanatory method by collecting survey data from customers of Islamic banks in Indonesia. PLS-SEM analysis tool with SmartPLS tool version 4 was utilized to search for hypothetical evidence. This study uncovered the effect of ease of use, efficiency, interoperability, privacy security, responsiveness, reliability, service cost, and service portfolio on ISBC customer satisfaction. In addition, among the significance of ISBC customer satisfaction on customer retention intention, there was a mediating effect of Islamic financial literacy. Islamic banks, consequently, must maintain a digital service system to meet customers' financial needs through quality control of system infrastructure and continuous network maintenance. Moreover, the demand for strategies to strengthen new digital services through adding features and promoting the advantages of digital financial services is needed to gain market share in the Indonesian financial market.